Krytycyzm „jaskiniowców” - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2025)
I am prompted to comment on criticism by its future and current forms, which I consider to be a form of expressing such primitive human instincts as the survival instinct, and such primitive human drives as the drive to reproduce and to control one’s immediate and distant surroundings. They occur not only in homo sapiens, but also in lower-ranking species, but in the former it can take on forms of expression that were and are considered by some to be evidence of its evolutionary development, while by others to remain at least in some respects the same. the level at which his ancestors who lived in the Paleolithic era were. I tend to agree with the latter rather than the former.